Development of basis sets to calculations of the electronic structure of YMnO3 - Treu, O.; Pinheiro, J. C.; Kondo, R. T.; Marques, RFC; Paiva-Santos, C. O.; Davolos, Marian Rosaly [UNESP]; Jafelicci, M. (Elsevier B.V., 2003)
The generator coordinate Hartree-Fock method was used to develop 20s17p, 30s20p14d, and 30s21p16d Gaussian basis sets for the O ((3)p), Mn (S-6), and Y (D-2) atoms, respectively. The Gaussian basis sets were contracted to 20s17p/9s7p, 30s20p14d/11s7p7d, and 30s21p16d/14s7p7d and utilized in calculations of total energy and orbital energies of the (MnO1+)-Mn-5 and (YO1+)-Y-3 fragments to evaluate its quality in molecular studies. Finally, the contracted basis set for O atom was supplemented with one polarization function of d symmetry and used along with the other contracted basis sets (for Mn and Y) to calculate dipole moments, total energy, and total atomic charges in YMnO3 in space group D-6h. The analysis of those properties showed that is reasonable to believe that YMnO3 present behavior of piezoelectric material. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Gaussian basis sets; contracted basis sets; dipole moments; total energy; total atomic charges; YMnO3